2017
DOI: 10.12740/app/76339
|View full text |Cite
|
Sign up to set email alerts
|

Relationship with siblings as a predictor of empathy and humor styles in early adulthood

Abstract: SummaryAims: Sibling relationships in early adulthood are explored relatively rarely. The aim of the current study was to describe this relationship and its importance for interpersonal functioning of young adults. Methods:The study included 100 participants at an average age of 27.08 years (SD=4.38); 60% were women (n=60) and 40% were men (n=40). The following tools were used in the study: Adult Siblings Relationships Questionnaire -Short Form, the Empathic Sensitiveness Scale and Humor Styles Questionnaire. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 14 publications
0
15
0
2
Order By: Relevance
“…This study expands on the limited amount of research that has been conducted on relationships with siblings during emerging adulthood (e.g., Milevsky, 2005Milevsky, , 2019Portner & Riggs, 2016;Scharf et al, 2005;Walęcka-Matyja, 2017) and the role of siblings on empathy development. Sibling relationships have been shown to be especially important for sisters (Ricklefs, 2015), as they tend to have closer relationships than other gender sibling combinations (Bedford & Avioli, 2001).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…This study expands on the limited amount of research that has been conducted on relationships with siblings during emerging adulthood (e.g., Milevsky, 2005Milevsky, , 2019Portner & Riggs, 2016;Scharf et al, 2005;Walęcka-Matyja, 2017) and the role of siblings on empathy development. Sibling relationships have been shown to be especially important for sisters (Ricklefs, 2015), as they tend to have closer relationships than other gender sibling combinations (Bedford & Avioli, 2001).…”
Section: Discussionmentioning
confidence: 96%
“…This might be because sibling interactions provide unique opportunities for individuals to recognize their own and others' emotions and contribute to each other's socialization (Dunn, 1998;Lam et al, 2012). The specific bond between siblings generates environments required for development of interpersonal relationships (Walęcka-Matyja, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These responses might depend on several variables such as different economic conditions, cultural, moral, educational and interpersonal behaviors, personal experiences, or levels of anxiety. 32,33 At this point, social relationships with siblings, quality of the relationships, and empathic behaviors related to providing support by siblings can make an impact in empathic care. 33 Supporting this phenomenon, in our study students with siblings demonstrated significantly higher empathy levels.…”
Section: Resultsmentioning
confidence: 99%
“…Female participants with a female sibling reported that they exerted more warmth towards their sibling than females with a male sibling (Barnes & Austin, 1995). Sistersister sibling dyads experience more warmth, intimacy, and emotional support while brother-brother sibling dyads experience more self-defeating humor (Welecka-Matyja, 2017).Women are also more likely to facetime their siblings than men are (Van Volkom et al, 2017). This may be due to society's double standards that women can show emotions while men should not engage in outward emotional expression.…”
Section: The Importance Of the Sibling Dyad And Birth Ordermentioning
confidence: 99%